Which type of tourism short video content inspires potential tourists to travel - Wu, Guihua; Ding, Xinyi (Frontiers in Psychology, 2023)
While user-generated short videos have become very common in tourism marketing, how they affect potential tourists’ decisions has not been discussed academically. Based on the customer inspiration theory, this study explored the effects of different tourism short video contents on potential tourists’ travel intentions, as well as the mediating effect of customer inspiration and the moderating effect of consumption orientation through three experiments. The following conclusions were drawn. (1) Tourism short videos significantly increased potential tourists’ customer inspiration and travel intention; (2) The customer inspirations (“inspired-by” and “inspired-to”) chain-mediated the relationship between tourism short videos and potential tourists’ travel intentions; (3) Consumption orientation positively moderated the chained mediation effect above, and the chained mediation effect of tourism short videos on the travel intentions of tourists with hedonistic motivations through inspire-by and inspire-to is stronger than that of tourists with utilitarian motivations. The above findings could help expand the perspective of tourism short video research and provide suggestions for tourism business managers to apply short video content to marketing.